Tracking aggregation behaviour and gel properties induced by structural alterations in myofibrillar protein in mirror carp (Cyprinus carpio) under the synergistic effects of pH and heating. (15th November 2021) - Du, Xin; Zhao, Mengna; Pan, Nan; Wang, Songping; Xia, Xiufang; Zhang, Dongjie
Highlights: Aggregation behavior of myofibrillar protein (MP) was affected by pH and temperature. Heating could promote the structural unfolding of MP. Aggregation and unfolding of MP at pH 6.0 was balanced during heating process. MP gel network structure was uniform and dense at pH 6.0 above 70 °C. Abstract: The synergistic effect of pH and heating on the structure, aggregation behaviour and gel properties of myofibrillar protein (MP) in mirror carp ( Cyprinus carpio ) was evaluated. The surface hydrophobicity of the control at pH 5.0 (143.6 ± 0.3 μg) was significantly higher than that of other samples ( P  < 0.05). Under the same pH conditions, the decrease in total sulfhydryl content of all samples during the heating process demonstrated that covalent/non-covalent cross-linking occurred between proteins due to heat input. Moreover, the decrease in solubility and the increase in turbidity of all samples verified the fact of MP aggregation, and the changes in the elasticity index (EI) and macroscopic viscosity index (MVI) also indicated a decrease in MP fluidity upon heating treatment. Therefore, the aggregation of MP was affected by pH and heating, and the optimal three-dimensional network structure and gel properties could be formed at pH 6.0 and above 70 °C.